The Association Between Environmental Factors and the Risk of Paediatric Inflammatory Bowel Disease - Elten, Michael (Université d'Ottawa / University of Ottawa, 2020)
Background: The incidence of inflammatory bowel disease (IBD) in children is increasing. Environmental factors related to industrialization, including increased levels of air pollution and reduced greenspace may be partially responsible. Methods: Health administrative data from Ontario were used to identify a cohort of children, and identify those diagnosed with IBD before the age of 18 years. Modelled exposures to air pollution (nitrogen dioxide, fine particulate matter, ozone, and oxidant capacity) and greenspace (through the normalized difference vegetation index) were obtained based on residential six-digit postal code. Results: Exposure to oxidant capacity during childhood and mid-pregnancy was associated with increased risk of IBD <18 years. No association for other pollutants was found. Residential greenspace during childhood was protective of paediatric-onset IBD, but no association with in-utero exposures was found. Conclusion: We observed significant relationships between environmental factors and paediatric-onset IBD. The novel finding of a protective effect of greenspace should be explored further.
Keywords: Air pollution; Greenspace; Inflammatory bowel disease; Epidemiology